THE EFFECT OF GIVING NATURAL FEED FROM CULTURES OF ROTIFERS (Brachionus sp.) TO GROWRTH OF WHITE SEAPER (Lates calcarifer) LARVA AND WATER QUALITY AT PT. BALI BARRAMUNDI, BULELENG DISTRICT, BALI - jayanti, shara (Politeknik Kelautan dan Perikanan Pangandaran, 2024)
This research was to determine the effect of providing natural food cultures of phytoplankton and rotifers in white snapper (Lates calcarifer) hatcheries on air quality at PT. Bali Barramundi Buleleng Regency, Bali. The rotifer culture will be successful in harvesting if there is sufficient food for the rotifer zooplankton (Brachionus sp.). One good food for rotifer growth is Chlorella sp. To get 500-700 rotifers/ml for 3 weeks with an initial inoculation of 10 birds/ml requires 5 million Chlorella sp cells/ml. The air used for rotifer zooplankton is sea air which is taken directly through 3 pumps connected to pipes installed in the sea at a distance of approximately 100 meters from the shoreline. The air that has been collected is added with chlorine at a dose of 25 ppm, then after stirring thoroughly, turn off the aeration in the tub. After 1x24 hours, add sodium thiosulfate at a dose of 0.125 ppm and turn on the aeration after a while. Before being given to larvae, rotifers and enriched first using Algamax, vitamin C at a dose of 2.5g/10 L for one hour. Rotifers are given with an initial density of 4-5 ind/ml (4,000-5,000 individuals/1,000L). Natural rotifer food is given twice a day for larvae (D2-D5) at 09.00 and 15.00 and given four times a day for larvae (D6-D25) at 08.00, 10.00, 14.00, 16.00 with a dose of (5-10 tail/ml). The results of spawning showed an average hatching degree (HR) of 65% - 90.5% and normal growth up to D25 with a length of 9.5 mm. The water quality test results obtained were temperatures ranging from (28 – 30)⁰ C, pH (7.5 – 8.5), DO (6.5-6.54) ppm, salinity (28 – 36) ppt, nitrate (2.6 – 3.2) ppm, phosphate 0.01 ppm and ammonia (0.05-0.06) ppm.